Preferential lithium extraction and simultaneous ternary cathode precursor synthesis from spent lithium-Ion batteries using a spray pyrolysis-based process - Zhou, Yongchao; Li, Yan; Chen, Ziyu; Zeng, Haibin; Su, Wenhao; Zhao, Zhao; Du, Chengming; Li, Chengzong; Li, Tao (Separation and purification technology, 2025)
[Display omitted] •A spray pyrolysis-based process for spent NCM recycling has been proposed.•Selectively Li recovery and ternary oxide precursor are simultaneously achieved.•Battery-grade Li2CO3 can be directly prepared from the water-leaching solution.•The leaching residue is high-quality precursor for synthesis of single-crystal NCM.•Regenerated single-crystal NCM811 retains 80 % capacity after 300 cycles at 1C. Spent LiNixCoyMnzO2 (NCM) recycling ensures the sustainable development of lithium-ion batteries (LIBs) industry by returning valuable metals back to the supply chain. However, traditional recovery techniques for extracting metals from spent NCM necessitate tedious separation and purification operations. Herein, a spray pyrolysis-based process has been proposed for spent NCM recycling, which achieves the preferential lithium (Li) extraction and ternary cathode precursor synthesis simultaneously. Specifically, after a process sequence ofchlorination roasting, spray pyrolysis, water leaching, spent NCM cathode powder is transformed into a LiCl solution and ternary oxide, which can be directly used for the synthesis of battery-grade Li2CO3 and NCM cathode, respectively. The pyrolysis behavior of different metal chloride solution is systematically examined and related thermodynamical mechanism is discussed. Besides, the residual Cl in the pyrolyzed powder is found to have a great influence on recovery efficiency and a corresponding Cl elimination method is proposed. Under the optimized conditions, >88 % of Li can be preferentially leached out and the regenerated single-crystal NCM811 retains 80 % capacity after 300 stable cycles at 1C. This work offers a short and robust process for obtaining high-value-added products from spent NCM cathode.